Pengaruh Kualitas Produk terhadap Kepuasan Konsumen di Usaha Kipang Sisera Panyabungan Kabupaten Mandailing Natal (Jurnal Manajemen Bisnis Digital Terkini, 2026)
This study aims to analyze the influence of product quality on consumer satisfaction in the Kipang Sisera Panyabungan Business. The research method used is a quantitative approach with data collection techniques through observation, interviews, and questionnaire distribution to 96 respondents who are customers of Kipang Sisera. The data obtained were analyzed using validity, reliability, and regression analysis tests with the help of SPSS 25. The results of the validity test showed that all items in the questionnaire were valid with a rtable value of > (0.1689), while the results of the reliability test using Alpha Cronbach showed a value of > 0.60, which means that the research instrument is trustworthy. The results of the partial regression test (t-test) showed that product quality had a positive and significant effect on consumer satisfaction with a significance value of 0.000 < 0.05. The determination coefficient (R²) test showed that product quality contributed 62.9% to consumer satisfaction, while the rest was influenced by other variables that were not studied in this study. These findings indicate that improving product quality, both in terms of taste, packaging, and quality consistency, is very important in maintaining consumer satisfaction and the sustainability of Kipang Sisera's business in the midst of market competition.